2016
DOI: 10.4103/0019-509x.204758
|View full text |Cite
|
Sign up to set email alerts
|

Detailed study of survival of patients with renal cell carcinoma in India

Abstract: This study has demonstrated the importance of factors such as tumor size, nuclear grade, and stage in the assessment of prognosis of RCC patients. More studies in India with more patients are needed to demonstrate the importance of these prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…Overall, 10% of the global population has kidney functioning problems. According to the National Institute of Diabetes and Digestive Kidney Diseases (NIDDK) (Abraham et al, 2016), as shown in Figure 1 in India, 7% of peoples are suffering from various kidney diseases. Figure 1 shows the different percentage of kidney diseases suffering people country-wise (Bhalla et al, 2017).…”
Section: Motivation For Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 10% of the global population has kidney functioning problems. According to the National Institute of Diabetes and Digestive Kidney Diseases (NIDDK) (Abraham et al, 2016), as shown in Figure 1 in India, 7% of peoples are suffering from various kidney diseases. Figure 1 shows the different percentage of kidney diseases suffering people country-wise (Bhalla et al, 2017).…”
Section: Motivation For Researchmentioning
confidence: 99%
“…Kidney Renal Cell Carcinoma (KRCC) is the most common kidney tumor, accounting for 2 to 3% of all new cases in India (Abraham et al, 2016). From country to country, the KRCC case varies, but the extreme western parts of the world affected are more.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations